Maternal Attitudes Toward Stunting: A Study During Pregnancy and Early Childhood Periods - Ramadanti Putri Mahanani; Maria Goretti Adiyanti; Wahyuni Kristinawati (Kuras Institute, 2026)
Stunting is a chronic nutritional problem among children under five, caused by prolonged malnutrition and recurrent infections, particularly during the first 1,000 days of life. Despite government programs such as supplementary feeding, stunting prevalence remains high. This study aims to understand the attitudes of high-risk pregnant women and mothers with stunted children. The data collection procedures and research approach have been clarified by specifying the qualitative case study design and the use of semi-structured interviews, observations, and document analysis. The participants included high-risk pregnant women in their first to third trimesters and mothers with children aged 0–5 years diagnosed with stunting. Participants were recruited after obtaining research approval from the faculty and relevant institutions. Eligible participants were identified and contacted through community health centers (Puskesmas) in accordance with the predefined inclusion criteria. The findings indicate that the success of stunting prevention in pregnant women and stunting management in mothers with young children is influenced by nutritional knowledge, positive maternal attitudes, and support from family, community health workers, and the government. Pregnant women emphasized prevention, while mothers with stunted children focused on improving their children’s condition. Based on the Theory of Planned Behavior, positive attitudes and behavioral control among mothers are key to forming healthy behaviors. Multi-stakeholder collaboration through nutrition education and support starting from pregnancy is crucial to reducing stunting.